1959
DOI: 10.1002/j.1537-2197.1959.tb06993.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the Embryo of Ginkgo Biloba Under Experimental Conditions. Iii. Growth Rates of Root and Shoot Upon Media Absorbed Through the Cotyledons

Abstract: Ball, Ernest. (North Carolina State Coll., Raleigh.) Growth of the embryo of Ginkgo biloba under experimental conditions. III. Growth rates of root and shoot upon media absorbed through the cotyledons. Amer. Jour. Bot. 46(2) : 130‐139. Illus. 1959.—Mature embryos of Ginkgo biloba were grown by inserting the cotyledons into agar medium containing one of the naturally‐occurring sugars of the seed. These sugars were utilized at 1, 2, 4, 8 or 16% (w/v). Root growth was best on the sugar‐mineral‐water media and occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1961
1961
1972
1972

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Hydrolysis of storage proteins provides a substrate for seedling growth. Studies on the in vitro culture of barley and Ginkgo embryos have shown that added glutamic acid may stimulate growth (2,12). When seed protein content is increased by N fertilization the levels of glutamic acid and proline, because of their dominance in storage protein, are increased to a greater degree than the other amino acids (19).…”
Section: Resultsmentioning
confidence: 99%
“…Hydrolysis of storage proteins provides a substrate for seedling growth. Studies on the in vitro culture of barley and Ginkgo embryos have shown that added glutamic acid may stimulate growth (2,12). When seed protein content is increased by N fertilization the levels of glutamic acid and proline, because of their dominance in storage protein, are increased to a greater degree than the other amino acids (19).…”
Section: Resultsmentioning
confidence: 99%
“…This had been expected since excised groundsel roots can be grown in White's medium, although previous workers have suggested that intact plants are unable to absorb or utilize sucrose through their roots (Spoehr, 1942;Went and Carter, 1948). Others (Bulard, 1952;Brown and Gifford, 1958;Ball, 1959) have found that sucrose is absorbed more readily by the cotyledons of gymnosperm embryos than by the radicle. This may be equally true for groundsel seedlings but when the cotyledons were immersed, just below the surface of the culture medium, growth was very abnormal.…”
Section: Discussionmentioning
confidence: 97%